STIGMA PETUGAS KESEHATAN TERHADAP PASIEN HIV/AIDS DAN PROBLEM SOLVING - Martiningsih Martiningsih; Abdul Haris; Ade Wulandari (poltekkes kemenkes mataram, 2015)
Abstract: HIV/AIDS is a disease which attacks the immune system and becomes pandemic in the entire region of Indonesia. The disease, in the last few years, shows the worrying increase of incidence number.The reported cumulative number of HIV by December 2013 is 127.416, while AIDS is 52.348 cases and the number of deaths caused by HIV/AIDS is 9.585 cases (Kemenkes RI, 2013). According to the cause of world population death in 2030, generally, the death caused by infectious disease decrease, while the death caused by HIV/IDS is continuous to increase. AIDS is still a scary thing to many people. In addition to medical reason, there are also many stigma attached to AIDS patients. Stigma towards AIDS patients also occurs in health service because the officer is afraid of getting infected by HIV when he/ she is treating the patients and it becomes an obstacle to the patients in getting the critical treatment and service treatment. The aim of this writing is to observe several references about the factors that influence the stigma towards HIV/AIDS patients.Some of the factors are being underestimated and getting bad judgment, the patient are not given the guarantees to obtain another facility, labeling to the patients, the excessive use of personal protective equipment to the patients, the incomplete HIV test, the inadequate pre and post counseling, there is no confidentiality guarantee of the test results to the family and medical staff who do not treat the patients, and the rejection of treatment.The efforts that can be done to decrease the stigma are assessing and increasing the knowledge and attitude towards HIV to the whole medical professionals, creating a secure working environment for medical staffs, using the participation and partnership approach, and conducting researches.